Profil Kondisi Fisik Atlet Bola Voli Universitas Sriwijaya - Arizky Ramadhan; Ahmad Luthfi Ramadhani; Iyakrus Iyakrus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study is to determine the physical condition of volleyball athletes at Sriwijaya University. The research method used is descriptive quantitative, employing instruments sourced from the Ministry of Youth and Sports, including flexibility (sit and reach), strength (push up, sit up, 10 hops left and right), power (vertical jump and medicine ball throw), speed (shuttle run), agility (20 m run), and endurance (beep test), with a sample consisting of male volleyball athletes from Sriwijaya University. The results of this study indicate that most components of the athletes’ physical condition are still in the poor to moderate categories, although some aspects have reached a good category. In conclusion, the overall physical condition of Sriwijaya University volleyball athletes still needs improvement, particularly in flexibility, endurance, and speed, in order to support more optimal performance. Keywords: Athletes, Physical Condition, Students, Volleyball.